Challenges in micro financing and introduction of Mosque based Ijarah Financing Model for micro enterprises using cash Waqf in Selangor state - Mohd Imtiyaz, Mohamed Noordeen; Abdul Razak, Dzuljastri; Kassim, Salina; Che Embi, Nor Azizan (2021)
Micro enterprises are one of the key sectors of economy of Malaysia. The Sector contributing significantly to the Gross Domestic Product (GDP) and providing employment opportunities to majority of workforce in the country. Despite its contribution towards the enhancement of wellbeing of the society and the continuous efforts from the government, micro enterprises are struggling with several prolonged issues. Considerable number of them are facing difficulties in obtaining financing as they rated as a market segment associated with high risk. Current economic recession as result of COVID-19 pandemic and various phases of continuous lock downs created huge negative impact on small businesses including microenterprises. As a result of that there is a need arise for special forms of innovative financial tools to serve the capital requirements of micro enterprises. This study suggests a mosque based sustainable model for financing micro enterprises using cash waqf with a significant feature of involving mosque-based administration committees (AJK) to intermediate between the Waqf Corporation of Selangor (PWS) and micro enterprises at village level. Using the Selangor state as the case study, this study employed quantitative approach by conducting a survey from 270 respondents based on Theory Planned Behaviour (TPB) to test the acceptance of the proposed model using SPSS. The results of Pearson correlation analysis found attitude, subjective norms and perceived behavioural control of micro entrepreneurs significantly influence the intention to use the suggested model. The model suggested by this study may be helpful in addressing challenges in financing inclusion faced by Micro enterprises and further improving welfare of the Muslim society by better usage of cash waqf. Contributions of this study may enlighten Islamic financial institutions, waqf administrators and policy makers for their strategic planning activities in designing Islamic Micro Finance